Rain Process Education as Interactive Multimedia in Early Childhood using the Multimedia Development Life Cycle (MDLC) - Yohani Setiya Rafika Nur; Dasril Aldo; Annisaa Utami (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
Learning media has a positive impact because it can be fun, increase students' interest in learning, and be interactive. The learning method in Early Childhood Education (PAUD) Ratnanigsih uses a Sentra approach and the environment by playing sambal learning to develop the intelligence of a potential child. The facts in PAUD Ratnaningsih found obstacles in the teaching and learning process. These obstacles occur due to the lack of visualization or media for teachers, and the absence of variations in learning can cause saturation in children. Users in this study are early childhood teachers in PAUD Ratnaningsih. Based on these problems, a learning press is needed for teacher and child relations educated at PAUD Ratnaningsih. The learning media design method in this study uses the Multimedia Development Life Cycle (MDLC) approach and learning media using Macromedia Flash 8. The results of this study are in the form of storyboard design, visualization of interface design, implementation of learning media, and testing with Blackbox Testing. Based on the conclusions of this study shows that all components and features of learning media function properly and can be used by teachers in the learning process "Universe" with the sub-theme "Rain".